2016
DOI: 10.1111/jonm.12421
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perspectives on how operational leaders influence function-focused care for hospitalised older people

Abstract: The findings provide direction on how leaders can facilitate function-focused care in the current health-care environment emphasising system efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 31 publications
2
29
0
2
Order By: Relevance
“…Hospitalisation increases the risk of functional decline for older people (Fox & Butler, 2016;Graf, 2006;Wang, Shamliyan, Talley, Ramakrish, & Kane, 2013;Zisberg, Shadmi, Gur-Yaish, Tonkikk, & Sinoff, 2015;Zisberg et al, 2011). Functional decline is the loss of ability to perform tasks, which can lead to older people to transition from hospital to residential care or long-term care after acute illness instead of returning to their homes (CIHI, 2017;Covinsky et al, 2003;Graf, 2006;Pedone et al, 2005;Sourdet et al, 2015;Wang et al, 2013).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Hospitalisation increases the risk of functional decline for older people (Fox & Butler, 2016;Graf, 2006;Wang, Shamliyan, Talley, Ramakrish, & Kane, 2013;Zisberg, Shadmi, Gur-Yaish, Tonkikk, & Sinoff, 2015;Zisberg et al, 2011). Functional decline is the loss of ability to perform tasks, which can lead to older people to transition from hospital to residential care or long-term care after acute illness instead of returning to their homes (CIHI, 2017;Covinsky et al, 2003;Graf, 2006;Pedone et al, 2005;Sourdet et al, 2015;Wang et al, 2013).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…It is reiterated that improvement and updating, with a view to optimizing the care provided, should be part of a permanent educational process (18) , leading to the safety of professionals who are motivated to use SOPs more frequently. In addition, managers should provide nursing professionals with continuing education opportunities to help them perform patient-centered care within a perspective of efficiency (19) . Nurses have a relevant role in PEH, and should stimulate and provide an environment conducive to discussion and clarification of the issues arising daily.…”
Section: Discussionmentioning
confidence: 99%
“…23 24 However, HCPs' perspectives on the acceptability of this warning signs intervention, as well as the barriers and facilitators to its delivery, are unknown. Prior studies have identified barriers (eg, lack of training, 26 limited experience 27 and poor communication 28 29 ) and facilitators (eg, HCP buy-in 29 and interprofessional collaboration 27 29 ) to TC in general, but they have not examined HCPs' perspectives on the specific, situated barriers and facilitators of a warning signs intervention in rural communities. Accordingly, this study builds on our previous research by examining HCPs' perspectives on this warning signs intervention for TC in rural communities.…”
Section: Overall Goalsmentioning
confidence: 99%
“…Then, telephone focus groups will be conducted at convenient times for HCPs by a research associate (RA) with doctoral preparation in qualitative methods and experience in conducting telephone focus groups. 26 The RA will explore HCPs' perspectives on the overall acceptability of the intervention and then, for each stratum, summarise HPCs' acceptability ratings of the intervention. Acceptability ratings that will be summarised are those of the individual stratum (ie, nurses, allied healthcare professionals and physicians) participating in the focus group discussion, not the whole sample.…”
Section: Open Accessmentioning
confidence: 99%